Contributions of prenatal care for the vaginal childbirth: mothers’ perception - Aleksandra Pereira Costa; Leila Alcina Correia Vaz Bustorff; Ana Rita Ribeiro da Cunha; Maria Cidney da Silva Soares; Verbena Santos Araújo (Rev Rene)
The educational actions focused on the construction of collective and shared knowledge in favor of labor/birth are among those included in the National Program for Humanization of Prenatal and Birth. This study aimed to analyze the way in which the prenatal follows the context of primary care in the health service network, contributing to the promotion of vaginal parturition, from the perception of primiparous puerperal women. It was an exploratory-descriptive study with qualitative approach, conducted at the Foundation Care in Paraiba-Brazil. The research participants were 30 women in the immediate post-partum period. We used the technique of thematic content analysis. It was noticed that the professionals who had performed the prenatal fail in their consummation causing disbelief and motivation in the pregnant women in relation to such practice; which makes them avoid opting for normal parturition. So, they miss the opportunities to adopt new practices and to build new knowledge, committed to the health of the patients and with the necessary changes in health services.